Functional outcome of total hip replacement using a short stem implant - Kapila, Rajiv; Lal, Mukand; Kapila, Preeti Takkar (International Journal of Research in Orthopaedics, 2019)
Background: Conventional cementless THA is associated with stress shielding of the proximal femur and thigh pain. Short femoral stem can conserve bone, reduce stress shielding in the femur and reduce thigh pain. The present study aims to describe the functional outcomes associated with short stem metaphyseal implant in THA in our department. Methods: This prospective study was conducted in the Department of Orthopaedic Surgery, Indira Gandhi Medical College, Shimla among patients who needed THA for painful disabling hip. Modified Harris hip scores (HHS) were assessed for all patients pre-operatively and at their final follow up. Results: During the study period, a total of 20 patients were included in the study, 20% of them were females. The most common indication for THA was avascular necrosis head of femur with secondary osteomyelitis (n=14), of which 12 cases had excellent Hip Harris Score while two were in good category. Modified Harris hip score was excellent in patients where early partial and full weight bearing was started. Per-operatively, there was only one complication of fracture greater trochanter which was fixed with cerclage wire. In early post-operative period, two cases of superficial infection were noted and one case of varus malposition was present. In late post operative period, there were three cases of varus malposition and one case of deep infection as sinus. Conclusions: Total hip replacement with short anatomical metaphyseal loading stem improved the modified Harris Hip score significantly, with very few complications. Future multicentric studies are needed to evaluate the efficacy of short stem implants over a long follow up period.